Factors Associated with Medication Adherence to Tuberculosis Preventive Therapy (TPT) Among Household Contacts in the Service Area of Paninggahan Primary Health Center, Solok Regency - Indrawadi .; Mustofa .; Asrul Fahmi (International Journal of Research and Review, 2026)
Background: Tuberculosis (TB) remains a major public health problem in Indonesia. Household contacts of TB patients are at high risk of acquiring TB infection and therefore require Tuberculosis Preventive Therapy (TPT). The success of the TPT program is highly dependent on medication adherence. Several factors, including knowledge, social support, treatment-related factors, and socioeconomic status, are presumed to influence adherence to TPT medication. Objective: To identify factors associated with adherence to TPT medication among household contacts of pulmonary TB patients in the working area of Paninggahan Primary Health Center, Solok Regency, in 2025. Methods: This study employed a quantitative analytic design with a cross-sectional approach. The study population consisted of 113 household contacts receiving TPT in the working area of Paninggahan Primary Health Center. Total sampling was applied. Data were collected using structured questionnaires and analyzed through univariate analysis, bivariate analysis using the Chi-Square test, and multivariate analysis using multiple logistic regression. Results: The findings revealed significant associations between knowledge (p=0.001; OR=6.083), social support (p=0.008; OR=5.121), treatment-related factors (p=0.009; OR=4.495), socioeconomic status (p=0.002; OR=3.750), and adherence to TPT medication. Multivariate analysis indicated that knowledge was the most dominant factor associated with TPT medication adherence, with an Exp(B) value of 5.553. Conclusion: Knowledge, social support, treatment-related factors, and socioeconomic status were significantly associated with adherence to TPT medication among household contacts of pulmonary TB patients. Knowledge was identified as the most dominant factor. Strengthening health education, family support, and healthcare worker assistance is recommended to improve adherence and enhance the success of the TPT program Keywords: Social Support, Adherence, Tuberculosis Preventive Therapy